2018
DOI: 10.1016/j.jsxm.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse Experiences and the COMT and MTHFR Genetic Variants Associated With Male Sexual Orientation in the Han Chinese Populations: A Case-Control Study

Abstract: Childhood abuse and the COMT and MTHFR genetic variants could be positively associated with the development of homosexuality. However, it remains unknown how these factors jointly play a role in the development of homosexuality, and more studies in different ethnic populations and with a larger sample and a prospective design are required to confirm our findings. Qin J-B, Zhao G-L, Wang F, et al. Childhood Abuse Experiences and the COMT and MTHFR Genetic Variants Associated With Male Sexual Orientation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…MTHFR is an important enzyme for folate metabolism, which is involved in the usability of the methyl donors by catalyzing the conversion of 5, 10-methylenetetrahydrofolate to 5methyltetra-hydrofolate, and plays an important part in the regulation of methionine to homocysteine in folate metabolism (35). MTHFR C677T polymorphism can lead to folate metabolism disorder, which is associated with infertility (36).…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR is an important enzyme for folate metabolism, which is involved in the usability of the methyl donors by catalyzing the conversion of 5, 10-methylenetetrahydrofolate to 5methyltetra-hydrofolate, and plays an important part in the regulation of methionine to homocysteine in folate metabolism (35). MTHFR C677T polymorphism can lead to folate metabolism disorder, which is associated with infertility (36).…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies were finally retained and overviewed in the present systematic review study. Seven studies ( Hamer et al, 1993 ; Hu et al, 1995 ; Rice et al, 1999a ; Mustanski et al, 2005 ; Ramagopalan et al, 2010 ; Sanders et al, 2015 ; Sanders et al, 2021a ) were linkage studies, four studies ( Macke et al, 1993 ; DuPree et al, 2004 ; Yu et al, 2015 ; Qin et al, 2018 ) utilized the candidate gene approach, and five studies ( Wang et al, 2012 ; Lawrance-Owen et al, 2013 ; Sanders et al, 2017 ; Ganna et al, 2019 ; Hu et al, 2021 ) were GWAS investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The latter study ( Qin et al, 2018 ) was designed as a case-control study of 537 exclusively homosexual men and 583 exclusively heterosexual men, with data collected from March 2013 to August 2015. Data were analyzed using χ 2 tests and logistic regression models, investigating the interplay of sociodemographic characteristics, childhood abuse experiences, and polymorphisms of COMT at rs4680, rs4818, and rs6267, and methylenetetrahydrofolate reductase (MTHFR) at rs1801133 on male homosexuality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the biologically based literature, it has been found that childhood abuse experiences are related to the development of sexual orientation and gender identity. Studies have shown an interaction between childhood sexual abuse and COMT polymorphisms and MTHFR genes in SGM men (O'Hanlan et al, 2018; Qin et al, 2018). When the diffusion-weighted magnetic resonance images of SGM individuals were examined, it was found that the microstructures of the white ores contained differences with male individuals, especially fetal testosterone excess and sexual dimorphic cognition and behavior correlated with corpus callosum asymmetry (O'Hanlan et al, 2018).…”
mentioning
confidence: 99%